(untitled) (Linguistics in Amsterdam, 2014)
“A written record of a speech event stands like a filter between the words as spoken and the analyst” (Schneider 2002: 67). The filter covering missionary sources typically consists of multiple layers, since they are produced by second language learners. Such missionary sources are generally consulted when they constitute the main source of data from that period. This is the case for Virgin Islands Dutch Creole (DC) and its 18th century documentation. I discuss four documented alternations, either in form or function, of the imperfective (and prospective) aspect markers (preverbal ‘le’ and ‘lo’), where it is not clear whether we are dealing with either the outcome of a linguistic change or a change in progress, or a case of (stable) inherent variation. By discussing the background of the author of the relevant sources, the audience design, and the speech community that the source is meant to reflect, an attempt is made for each alternation to resolve the issue of whether we are dealing with change or variation and to overcome the challenges posed by the ‘filter’ over the data.